2014
DOI: 10.1586/14779072.2014.952283
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac death and obesity

Abstract: For individuals and the society as a whole, the increased risk of sudden cardiac death in obese patients is becoming a major challenge, especially since obesity prevalence has been increasing steadily around the globe. Traditional risk factors and obesity often coexist. Hypertension, diabetes, obstructive sleep apnea and metabolic syndrome are well-known risk factors for CV disease and are often present in the obese patient. Although the bulk of evidence is circumstantial, sudden cardiac death and obesity shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 104 publications
1
43
1
3
Order By: Relevance
“…Regarding anthropometrics, obesity and being overweight represent a predictor of cardiac functions' impairment. A higher number of PVCs and reduced HRV have been documented in obese subjects [16]. Additionally, a recent research study identified the waist-to-hip ratio, a marker of visceral adiposity, to be associated with HRV [17].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding anthropometrics, obesity and being overweight represent a predictor of cardiac functions' impairment. A higher number of PVCs and reduced HRV have been documented in obese subjects [16]. Additionally, a recent research study identified the waist-to-hip ratio, a marker of visceral adiposity, to be associated with HRV [17].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is associated with an increased risk for cardiovascular diseases and premature death [1,2]. An abnormal ventricular repolarization, which predisposes to sudden death upon cardiac arrhythmia [3], may contribute to the increased mortality risk since obesity has been found to be associated with a high prevalence of a prolonged QT interval in electrocardiographic (ECG) recordings [4].…”
Section: Introductionmentioning
confidence: 99%
“…increased risk of atrial and ventricular arrhythmias. 10,11 Furthermore, several studies suggested that obesity per se was associated with an increased risk of SCD. 12,13 In the Atherosclerosis Risk in Communities study, 12 obesity was related to the incidence of SCD over a 12.6 year follow-up.…”
Section: Accepted Manuscriptmentioning
confidence: 99%